Bullying and Social Support in Elementary School Students: A Qualitative Study - Fadjrina Hapsari Woro Ayuningbudi; Yuliana Hanami (Psympathic : Jurnal Ilmiah Psikologi, 2023)
This descriptive qualitative study aimed to comprehend the perception of elementary school children in Bandung about bullying, focusing on the understanding of the phenomenon and the use of social support from teachers, parents, and peers. In order to achieve this aim, semi-structured interviews were carried out with four children aged between 12 to13 years, from different elementary schools in Bandung. The data obtained from the conducted interview were subsequently transcribed and analyzed using a thematic analysis framework. The analysis results showed children comprehended bullying differently in a manner that did not entirely harmonize with the conventional definition. It was also important to acknowledge that children viewed emotional support as a more important factor compared to direct problem-solving. The obtained results were extensively discussed to explore implications for further analysis concerning the interplay between bullying and the association with social support.